Sodium butyrate does not decrease the evolution of precancerous lesions in rats - Silva,Fernanda Guimarães Drummond e (2010)
PURPOSE: To evaluate the preventive effect of sodium butyrate in the appearance of aberrant crypt foci (ACF) in rats after induction with the carcinogen 1,2-dimethylhydrazine (DMH). METHODS: Forty Wistar rats were separated into four groups (n=10) distributed as follows: control 1, control 2, butyrate 1 and butyrate 2. The groups control 1 and butyrate 1 remained under experimentation for 4 weeks, while the groups control 2 and butyrate 2 remained for 8 weeks. In the first four weeks, the animals of the control groups received water ad libitum and the animals of the butyrate groups received a sodium butyrate solution (3.4%) ad libitum. Injections of the drug 1,2-dimethylhydrazine were applied during the two first weeks of the experiment in all the animals, concurrently with the application of sodium butyrate. The large intestine of the animals was removed, for the analysis of the ACF and of the content of polyamines. The animal feces were collected for the analysis of the SCFA profile. RESULTS: The spermidine presented a higher concentration in the group butyrate 2 in comparison to the group control 2. There was a significant difference in the concentration value (µmol/mL) of acetate in comparison to the groups control 2 and butyrate 2. CONCLUSION: The use of sodium butyrate together with the induction of colorectal cancer was not effective in the prevention of the disease progression.